2022
DOI: 10.1007/s10853-022-07354-x
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Si oxidation mediated by annealing temperature and atmosphere

Abstract: The morphology evolution by thermal annealing induced dewetting of gold (Au) thin films on silicon (Si) substrates with a native oxide layer and its dependences on annealing temperature and atmosphere are investigated. Both dewetting degree of thin film and Au/Si interdiffusion extent are enhanced with the annealing temperature. Au/Si interdiffusion can be observed beyond 800 °C and Au–Si droplets form in both argon and oxygen (Ar + O2) and argon and hydrogen (Ar + H2) environments. In Ar + O2 case, the passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The formation of the circular cavities can be attributed to the decomposition of the SiO 2 layer at high temperature in reducing atmosphere. It has been reported after the annealing of Au thin films deposited on SiO 2 /Si substrates with different thicknesses of the SiO 2 layer [ 3 4 36 ]. The active oxidation of Si also occurs once the Si substrate is exposed [ 2 3 37 ], which can be proved by the calculated oxygen partial pressure ( Supporting Information File 1 ) and the much greater average depths of cavities (more than 600 nm) compared with the thickness of the SiO 2 layer (300 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the circular cavities can be attributed to the decomposition of the SiO 2 layer at high temperature in reducing atmosphere. It has been reported after the annealing of Au thin films deposited on SiO 2 /Si substrates with different thicknesses of the SiO 2 layer [ 3 4 36 ]. The active oxidation of Si also occurs once the Si substrate is exposed [ 2 3 37 ], which can be proved by the calculated oxygen partial pressure ( Supporting Information File 1 ) and the much greater average depths of cavities (more than 600 nm) compared with the thickness of the SiO 2 layer (300 nm).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the reason why the Pt thin film as thick as 10.8 nm could be fully dewetted to isolated Pt NPs without any substrate perturbation when using Ar or H 2 flow as compared to only partial dewetting occurred for Pt films thicker than 1.4 nm when under vacuum, and the observation that the two different flowing gas of Ar and H 2 had similar effect on the thermal dewetting behavior of Pt thin films, the role of residual O 2 during the thermal dewetting process was investigated. Previous studies have shown that oxidation of the Si substrates occurred in the thermal annealing in ultrapure Ar + H 2 52 and ultrapure N 2 53 environment due to the presence of a small amount of residual O 2 present. To examine whether there is the formation of SiO 2 due to the thermal oxidation in our thermal dewetting processes, a bare Si substrate with a 2.3 nm native SiO 2 surface layer was placed under the similar condition used at 950 °C with 100 sccm H 2 for a duration varying from 15 to 90 min.…”
Section: Effect Of Residual Oxygen On the Morphology Evolution In The...mentioning
confidence: 99%
“…It is worth noting that, in the presence of air, chemical changes in the W structures are expected to take place at temperatures above 650 °C [ 20 ]. While it is well known that Si-SiO 2 interfacial systems are unstable at high temperatures [ 21 , 22 ], it is also important to monitor low-temperature processes in the context of nanostructured systems. To monitor these temperature-induced changes, Fourier transform infrared spectrometry (FTIR) has been applied as a monitoring method to determine changes in the polar bonds within SiO 2 [ 23 ] and SiO 2 -W structures [ 24 ].…”
Section: Introductionmentioning
confidence: 99%